Perceived anabolic–androgenic steroid use is associated with perceived neuroticism. (3rd May 2016) - Sagoe, Dominic; Huang, Kristin; Molde, Helge; Andreassen, Cecilie S.; Pallesen, Ståle
Abstract: Ratings of the perceived personality (Five-Factor Model) of an anabolic–androgenic steroid(s) (AAS) user, an erythropoietin (EPO) user, a protein powder user and a nonuser of these ergogenic aids were investigated. The sample of 328 (236 females) non-substance use participants providing the ratings was students aged 18–52 years. They were drawn from three Norwegian higher education institutions and were randomized to four independent experimental conditions, each comprising a specific scenario/description [food ( n = 82), protein powder ( n = 83), EPO ( n = 83), and AAS ( n = 80)] similar in number, age and gender distribution. Participants in all conditions rated their protagonist on the NEO Five-Factor Inventory. Multivariate analysis of variance results indicated, consistent with our prediction, that the protagonist who consumed food was perceived as least neurotic whereas the AAS and EPO protagonists were rated similarly on neuroticism. The food and protein powder protagonists were rated similarly on openness albeit higher than the EPO protagonist. The food protagonist was regarded as more agreeable than protagonists of the ergogenic aids. Our findings indicate that perceived AAS use negatively impacts the construal of the perceived user's personality or social image. Implications of findings are discussed.